Ternary structure of Plasmodium vivax N-myristoyltransferase with myristoyl-CoA and inhibitor IMP-0001173 - Bolling,C; Mendez,A; Taylor,S; Makumire,S; Reers,A; Zigweid,R; Subramanian,S; Dranow,DM; Staker,B; Edwards,TE; Tate,EW; Bell,AS; et al. (Acta Crystallographica Section F: Structural Biology Communications, 2024)
Plasmodium vivax is a major cause of malaria, which poses an increased health burden on approximately one third of the world's population due to climate change. Primaquine, the preferred treatment for P. vivax malaria, is contraindicated in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency, a common genetic cause of hemolytic anemia, that affects ∼2.5% of the world's population and ∼8% of the population in areas of the world where P. vivax malaria is endemic. The Seattle Structural Genomics Center for Infectious Disease (SSGCID) conducted a structure–function analysis of P. vivax N-myristoyltransferase (PvNMT) as part of efforts to develop alternative malaria drugs. PvNMT catalyzes the attachment of myristate to the N-terminal glycine of many proteins, and this critical post-translational modification is required for the survival of P. vivax. The first step is the formation of a PvNMT–myristoyl–CoA binary complex that can bind to peptides. Understanding how inhibitors prevent protein binding will facilitate the development of PvNMT as a viable drug target. NMTs are secreted in all life stages of malarial parasites, making them attractive targets, unlike current antimalarials that are only effective during the plasmodial erythrocytic stages. The 2.3Å resolution crystal structure of the ternary complex of PvNMT with myristoyl-CoA and a novel inhibitor is reported. One asymmetric unit contains two monomers. The structure reveals notable differences between the PvNMT and human enzymes and similarities to other plasmodial NMTs that can be exploited to develop new antimalarials.